Klasifikasi Emosional Anak Berkebutuhan Khusus Secara Akademik - Abdul Satar; Alvin Raynaldi; Dhea Andeti Putri (Lembaga Pengembangan Kinerja Dosen, 2024)
Children with special needs are special children, some of them still need help from other people to carry out their daily activities. But of course children with special needs are trained and accustomed to being independent. There are many Sufistic values ​​contained in daily actions, including in the process of forming emotional independence in crew members. The aims of this research include: to determine the emotional classification of children with special needs (ABK) academically. This research uses field methods (field research) with a qualitative approach. The data collection techniques were obtained through the process of observation, interviews and documentation. The subjects in this research were the founder, several teachers and several students. The results of this research show that: emotional classification of children with special needs (ABK) academically at SLBN Muara Bungo. In delivering it through activities outside the classroom and inside the classroom by first providing an example and motivation to the child then the child will practice periodically and do it with the help of other people first and then be left to do whatever they can on their own. This is a form of independent behavior for children with special needs. (ABK) includes emotional independence, namely controlling one's own emotions, and the effectiveness of instilling Sufistic values ​​in forming emotional independence for children with special needs (ABK), including repentance, responsibility, trust and patience, even though independence is still with the help of other people.